PENGARUH DERIVATIF KEUANGAN DAN FINANCIAL LEASE TERHADAP TAX AVOIDANCE - Eka Sundari; Nofryanti Nofryanti (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: The Study aims to find out the influence of financial derivatives and financial leases tax avoidance. Sample in this studiy is 28 manufacturing companies with the criteria of disclosing financial statements for 2014-2016 which were listed on the Indonesia stock exchange. Technical analysis in this research uses multiple regression with SPSS testing. The results shows that financial derivatives and financial leases significantly influence tax avoidance. Keywords: Company Size , Financial Derivatives, Financial Lease, ROA, Tax Avoidance